Psychometric Properties of the Arabic Version of Interactive Breastfeeding Scale - Ghafel, Hawraa (Journal of Contemporary Medical Sciences, 2024)
Objective: To assess factors influencing mother-child interaction during breastfeeding and validate the Arabic version of the Interactive Breastfeeding Scale (IBfS). Methods: A descriptive (cross- sectional study design) was carried out to evaluate the factors that interfere with the mother-child interaction during breastfeeding. A non-probability 'purposive sample' consists of (377) mothers who attending primary health care centers in Baghdad City. The study was started at January/2024 to July / 2024. Results: The Arabic version of the Interactive Breastfeeding Scale reveals strong psychometric properties with Cronbach’s Alpha values ranging from 0.71 to 0.86. Significant correlations were found between the scale and factors like Mother’s Perspective (r = .886) and Child Perspective (r = .661). The findings highlight the importance of mother and child-related factors in breastfeeding experiences. Conclusions: The Arabic version of the Interactive Breastfeeding Scale (IBfS) demonstrates strong reliability and validity, making it a robust tool for assessing breastfeeding dynamics. Key factors such as Mother’s Perspective and Child Perspective show significant correlations with IBfS, underscoring their critical role in the breastfeeding experience. The scale’s psychometric properties support its use in diverse settings, providing valuable insights into mother-child interactions during breastfeeding.